2017
DOI: 10.1126/science.aah5825
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteri induces gut intraepithelial CD4 + CD8αα + T cells

Abstract: The small intestine contains CD4+CD8αα+ double-positive intraepithelial T lymphocytes (DP IELs), which originate from intestinal CD4+ T cells through downregulation of the transcription factor ThpoK and have regulatory functions. DP IELs are absent in germ-free mice, suggesting that their differentiation depends on microbial factors. We found that DP IEL numbers in mice varied in different vivaria, correlating with the presence of Lactobacillus reuteri. This species induced DP IELs in germ-free mice and conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
395
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 640 publications
(414 citation statements)
references
References 50 publications
14
395
1
4
Order By: Relevance
“…The prevention of liver damage by non-absorbable antibiotics was associated with restored expression of Il22 mRNA in lamina propria cells and IL-22 production by ILC3 on IL-23 stimulation (figure 4D,E). Mechanistically, we observed that antibiotics treatment was associated with increased intestinal levels of the AHR ligand indole-3-lactic acid,17 while IAA and indole-3-aldehyde levels did not significantly change (see online supplementary figure S4e–g). These data support that impaired intestinal IL-22 production results from ethanol-associated dysbiosis causing altered tryptophan catabolism and AHR ligand production.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The prevention of liver damage by non-absorbable antibiotics was associated with restored expression of Il22 mRNA in lamina propria cells and IL-22 production by ILC3 on IL-23 stimulation (figure 4D,E). Mechanistically, we observed that antibiotics treatment was associated with increased intestinal levels of the AHR ligand indole-3-lactic acid,17 while IAA and indole-3-aldehyde levels did not significantly change (see online supplementary figure S4e–g). These data support that impaired intestinal IL-22 production results from ethanol-associated dysbiosis causing altered tryptophan catabolism and AHR ligand production.…”
Section: Resultsmentioning
confidence: 86%
“…Mice on the chronic–binge ethanol diet had lower mean amounts of IAA (figure 2B), a microbiota-dependent AHR ligand16 and indole-3-sulfate (figure 2C) in the small intestine. Levels of other potential AHR ligands such as tryptamine (figure 2D), indole-3-aldehyde (figure 2E), indole-3-acetamide (figure 2F), a precursor of IAA and indole-3-lactic acid17 (figure 2G) did not differ significantly between mice fed the ethanol versus the control diet. These data indicate that ethanol feeding reduces microbiota-dependent production of AHR ligands from tryptophan, which could be responsible for the reduced IL-22 production.…”
Section: Resultsmentioning
confidence: 99%
“…This metabolite and related bacterial compounds (indole-3-aldehyde, indole-3-lactate, and indole-3-propionate) were previously shown to reduce intestinal inflammation and to prevent gut barrier dysfunction (19, 25, 26, 3538). In the present study, we show for the first time that indole alleviates inflammation in the liver, away from the gut.…”
Section: Discussionmentioning
confidence: 99%
“…The converted CD4 + CD8αα + TCRαβ + IELs lose expression of T helper-inducing POZ/Krüppel-like factor (THPOK; also known as ZBTB7B), turn on expression of Runt-related transcription factor 3 (RUNX3) and T cell-specific T box transcription factor T-bet (also known as TBX21) and upregulate expression of IEL-associated genes such as natural killer (NK) cell receptor 2B4 and granzyme B 14,19,20 . This process is mediated in part by microbial metabolites, including indole derivatives from Lactobacillus reuteri , that activate aryl hydrocarbon receptor (AHR) 21 . Intriguingly, this conversion can be observed among lamina propria regulatory T (T reg ) cells, which subsequently migrate to the intestinal epithelium, lose expression of forkhead box protein P3 (FOXP3) and THPOK and become CD4 + CD8αα + IELs in a microbiota-dependent manner 22 .…”
Section: Conventional Intestinal Ielsmentioning
confidence: 99%